Analisisifaktor Penyebab Ketidaksesuaian Data Stock Opname Barang Consumable Menggunakan Metode Dmaic Di PT Xyz - Simon B. Saitama Purba; Endang Pudji Widjajati (Jupiter: Publikasi Ilmu Keteknikan Industri, Teknik Elektro dan Informatika, 2024)
Stock-taking is one way to maintain stock inventory by physically counting the stock of goods in the warehouse. However, it is not uncommon for companies to face data mismatches between existing records in the system and actual conditions in the warehouse on an ongoing basis. This problem can cause losses for the company in terms of quality, quantity, and storage costs. The DMAIC method (Define, Measure, Analyze, Improve, Control) is one method that can be used to overcome this problem. Based on data processing, it is obtained that the causes of stock-taking mismatches are outgoing goods that have not been inputted in the system, returns of goods that have not been inputted in the system, errors in inputting incoming goods into the system, different part numbers, incoming goods have not been inputted in the system with the largest percentage of causes being outgoing goods that have not been inputted at 49.60%. As for one of the efforts to control stock-taking discrepancies by making reports based on stock-taking deviation data within a certain period of time so that it can continue to reduce the occurrence of stock-taking discrepancies.